2007
DOI: 10.1007/bf02912890
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress is the primary event: Effects of ethanol consumption in brain

Abstract: Damaging effects of reactive oxygen species on living systems are well documented. They include oxidative attack on vital cell constituents. Chronic ethanol administration is able to induce an oxidative stress in the central nervous system. In the present study, 16-18 week-old male albino rats of Wistar strain were exposed to different concentration of ethanol for 4 weeks. This exposure showed profound effect on body weight. Ascorbic acid level; and activities of alkaline phosphatase and aspartate transaminase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 27 publications
0
20
0
1
Order By: Relevance
“…This is due to the fact that these enzymes are released into the blood when the body suffers some kind of injury (Khan et al 2013). However, unlike CK, increased activities of AST and ALT are observed in animals under stress (Kumar Das et al 2007;Mokondjimobe et al 2012;Ismail et al 2013).…”
Section: Introductionmentioning
confidence: 94%
“…This is due to the fact that these enzymes are released into the blood when the body suffers some kind of injury (Khan et al 2013). However, unlike CK, increased activities of AST and ALT are observed in animals under stress (Kumar Das et al 2007;Mokondjimobe et al 2012;Ismail et al 2013).…”
Section: Introductionmentioning
confidence: 94%
“…Cerebral oxidative stress was induced in rats by feeding 20% ethanol (5 ml/100gbw) for a period of 28 days (Saravanan et al, 2003;Das et al, 2007). Animals were divided into 6 groups consisting of six animals each.…”
Section: Experimental Animals and Designmentioning
confidence: 99%
“…On the other hand, observed gradual increase in GR activity in different ethanol groups (Table 3) suggested that cerebrum was compensating the level of GSH, however, as it was observed in Table 1, the cerebrum failed to compensate the GSH level and thereby the pro-oxidant status prevailed in cerebrum. Likewise, Das et al [20] noted the gradual increase in pro-oxidant status of brain upon exposure to ethanol; however, they found a reduction in GPx activities. Co-exposure of aluminum compromised this compensatory process of cerebrum and made it more vulnerable to oxidative stress.…”
Section: Discussionmentioning
confidence: 95%
“…To estimate the level of lipid peroxidation, the levels of malondialdehyde formation in cerebrum were measured as A 535 of supernatant fluid of a mixture of tissue homogenate, trichloroacetic acid, thiobarbituric acid after heated for 15 min at 80°C. The activities of catalase, superoxide dismutase, glutathione reductase and glutathione peroxidase were assayed following the spectrophotometric methods as quoted by Das et al [20]. For estimation of catalase activities, assay systems were prepared by mixing 1.90 mL of 0.05 M sodium phosphate buffer (pH 7.0), 0.1 mL cerebrum homogenate and 1.0 mL of 0.05 M Hydrogen peroxide in phosphate buffer.…”
Section: Tissue Collection and Biochemical Estimationmentioning
confidence: 99%